Abstract ID: 366 Coherent and non-coherent phototherapy. (December 2018) - Fusi, F.; Romano, G.
Abstract : Light has been used therapeutically for thousands of years. In ancient Egypt, sunlight was considered as a medicine, used for its healing power and, even recommended in one of the oldest surviving Egyptian medical texts: the Ebers Papyrus. The ancient Greeks were the first to write about the importance of sunlight in human health: the Athenian physician Hippocrates prescribed heliotherapy (sunbathing) for both medical and psychological purposes, even if with very little objective evidence supporting its purported therapeutic evidence. Only in the late 17th century light therapy was based upon scientific principles, providing the basis for a more reliable understanding of the relationship between humans and sunlight. In 1735, Fiennius described a case in which he cured a cancerous growth on a patient's lip using a sunbath [1]. In 1774, Faure reported that he successfully treated skin ulcers with sunlight [2], and in 1776 LePeyre & LeConte found that concentrated sunlight accelerated wound healing and destroyed tumors [3]. Continuing research generated a growing medical interest in the potential effects of light to treat and cure skin diseases. This culminated in the awarding of the 1903 Nobel Prize in Medicine to Niels Finsen for his pioneering work showing that light could successfully treat cutaneous mycobacterium tuberculosis (lupus vulgaris). Modern phototherapy developed in the late 20th century with the advance of LASERs, high-pressure arc lamps and LEDs, which represent key technologies for both non-invasive diagnosis and effective treatment in contemporary medicine. Coherent and non-coherent irradiation induce biological effects in tissues mainly through photochemical, photothermal and photomechanical interactions. In this presentation, we will focus on the photochemical and photothermal effects, presenting their main applications of clinical importance. In addition to more established techniques and applications (e.g. in photo-dermatology and opthalmology), we will consider also innovative systems to perform phototherapy in two exemplary applications, namely antibacterial and anti-tumoral phototherapies in internal organs/districts [4]. These hold the promise to be minimally invasive and patient-compliant. Besides, antibacterial light therapies can actively contribute in solving the great issue of antibiotic resistance.